2022
DOI: 10.1088/1674-4527/ac712e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Coronal Green-line Intensities with the EUV Measurements from SDO/AIA

Abstract: The intensity of the green line (Fe XIV 5303 \AA) is the strongest in the visible spectrum of the solar corona,}} and this line has been used as long-term powerful diagnostic tools for studying the coronal configurations and hot plasma dynamics. However, it is an open question if there exists close relationship between the green line intensities and the coronal EUV line emissions for various coronal structures. In this paper, we use the green-line data by the Lijiang YOGIS Lyot coronagraph and the EUV data fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Using this instrument, Zhang et al (2022a) found that the coefficients between the green line coronal data and the 211 Å data of SDO/AIA (Lemen et al, 2012) always keep the high values. Zhang et al (2022b) also suggested that the correlation between the coronal green line and the magnetic field is strong.…”
Section: Experimental Conditions and Instrumentsmentioning
confidence: 95%
“…Using this instrument, Zhang et al (2022a) found that the coefficients between the green line coronal data and the 211 Å data of SDO/AIA (Lemen et al, 2012) always keep the high values. Zhang et al (2022b) also suggested that the correlation between the coronal green line and the magnetic field is strong.…”
Section: Experimental Conditions and Instrumentsmentioning
confidence: 95%